Pengaruh Video Sebagai Media Pembelajaran Terhadap Minat Dan Motivasi Belajar Siswa Kelas Viii Smp Nurul Mustofa Tanjungbumi Kabupaten Bangkalan - Abror, Aisul; Huda, Nuril; Sunardjo, Sunardjo (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
Problems related to interest in learning are: students’ interest in learning as a whole has not been formed, lack of identifying and knowing their interests and talents in learning, interest that has not been directed properly either by the students themselves or by external parties, interest that has not been explored properly in learning, students' interests are not implemented enough to achieve the goals of their interests. Analyzing the influence of video as a learning medium on the learning motivation of class VIII students at Nurul Mustofa Tanjungbumi Middle School, Bangkalan Regency. The design in this research used quantitative research. Quantitative research is research that emphasizes objective phenomena with a survey approach or other measurements that are described with quantitative numbers. Based on Table 1, the data obtained shows that the Fcount value is 3.300. After the Fcount value is obtained, the next step is to determine the Ftable value. In determining the Ftable value. The level of significance in this research is 0.05, df 1, namely df 1 = (number of variables-1) becomes df 1 = (3-1) = 2, and df 2 is 23, obtained from (df) = n-k-1. N is the number of research samples and k is the number of independent variables in the research, so df = 26-2-1=23. Thus, the Ftable value is 1.161. The test results show that Fcount > Ftable (3,300 > 1.161). It can be concluded that there is a significant influence of video-based learning media on interest and motivation to learn.